RP- HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF METOLAZONE AND RAMIPRIL IN ORAL SOLID DOSAGE FORM - DEVIKA.G.S; M. SUDHAKAR; J.VENKATESHWARA RAO (International Journal of Pharma and Bio Sciences, 2012)
A Simple, efficient and reproducible reverse phase high performance liquid chromatographic method was developed and validated for the Simultaneous determination of metolazone (MET) and ramipril (RAM) in combined dosage form. The separation was effected on a Hypersil ODS C18 column (250 mm x 4.6 mm;5µ) using a mobile phase mixture of 30mM sodium dihydrogen phosphate buffer adjusted to pH 2.5.0 with orthophosphoric acid and acetonitrile in a ratio of 40:60 v/v at a flow rate of 1.0ml/min. The detection was made at 242 nm. The retention time of metolazone and ramipril was found to be 4.140± 0.007min and 7.007± 0.006min. Calibration curve was linear over the concentration range of 10-70 µg/ml for bothMetolazone and Ramipril .All the analytical validation parameters were determined and found in the limit as per ICH guidelines, which indicates the validity of the method. The developed method is also found to be precise, accurate, specific, robust and rapid for the simultaneous determination of Metolazone and Ramipril in tablet dosage forms.